Unmet needs of biochemical biomarkers for human prion diseases - Peter Hermann; Inga Zerr (Prion)
Although the development of aggregation assays has noticeably improved the accuracy of the clinical diagnosis of prion diseases, research on biomarkers remains vital. The major challenges to overcome are non-invasive sampling and the exploration of new biomarkers that may predict the onset or reflect disease progression. This will become extremely important in the near future, when new therapeutics are clinically evaluated and eventually become available for treatment. This article aims to provide an overview of the achievements of biomarker research in human prion diseases, addresses unmet needs in the field, and points out future perspectives.